Medication Adherence Monitoring Using Smartphone Video Dosing in an Open-label Pilot Study of Monthly Naltrexone Plus Once-daily Bupropion for Methamphetamine Use Disorder: Feasibility and Acceptability. Issue 5 (September 2019) - Walker, Robrina; Hillhouse, Maureen; Perrochet, Brian; Sparenborg, Steven; Mooney, Larissa; Ling, Walter
Abstract : Objectives: This article describes how smartphones were used to monitor and encourage medication adherence in a pilot study evaluating the potential efficacy of a combination pharmacotherapy for methamphetamine use disorder. We examine the feasibility, utility, and acceptability of using smartphones to capture dosing videos from the perspectives of participants and staff. Methods: The study was an 8-week, open-label evaluation of extended-release injectable naltrexone combined with once-daily oral extended-release bupropion (BRP, Welbutrin XL, 450 mg/day). Participants attended visits twice-weekly for observed BRP dosing, assessments, and medical management. BRP was dispensed once weekly for dosing on nonclinic days. Medication adherence was assessed objectively (by observation in the clinic and smartphone videos for dosing at home) and subjectively (self-reports of dosing). Surveys assessing the smartphone component were completed by participants and study staff. Results: Participants (N = 49) reported taking 93.6% of the dispensed BRP doses while 86.6% of dispensed doses were confirmed via dosing video and in-person observations. Most participants who completed the survey agreed that the smartphone was easy to use (92.6%) and that taking the dosing videos helped to remember to take the study medication (80.5%). Staff agreed that the smartphone helped collect accurate dosing data for most (77.5%) participants. Conclusions: The use of smartphones for video-based oral medication dosing in this study provided a feasible and acceptable mechanism to encourage, monitor, and confirm medication adherence. Video-confirmed dosing adherence provides an objective numerical indicator of the lowest medication adherence rate participants achieve, allowing investigators to more confidently interpret results.